(untitled) (Scientific journal of the Fergana State University, 2024)
The longhorn beetles are widespread dendrophagous insects in all regions of Uzbekistan, and a total of 27 species and subspecies belonging to 5 subfamilies, 15 tribes, 20 genera and 11 subgenera were recorded. The current checklist of the longhorn beetles was compiled for the first time for Uzbekistan, and is of important for investigating the fauna and distribution of these beetles, as well as, is also of great scientific and practical importance in determining effective measures to fight against pest species.